THE WAKAF BENEFITS OF SHARIA SHARES AS PRODUCTIVE WAQF MODERNIZATION: COMPARATIVE STUDY OF INDONESIA AND MALAYSIA - Choiriyah, Ana Laela Fatikhatul; Imaduddin, Muhammad; Setyawan, Fendi; Prakoso, Bhim (Faculty of Law, Universitas Pekalongan, 2024)
Waqf, as an important form of financial worship, has significant economic potential and has evolved from traditional forms such as land and buildings to innovations like cash waqf, which is more flexible for developing productive enterprises. Although the potential for cash waqf in Indonesia is very high, reaching Rp180 trillion per year according to the Indonesian Waqf Board, its management is not yet optimal. The aim of this research is to analyze and compare the development of Sharia stock benefit waqf as a form of productive waqf modernization in Indonesia and Malaysia, and to identify its development potential to increase the effectiveness and benefits of waqf in the context of modern Islamic economics. This research uses normative legal research methods with statutory and conceptual approaches, focusing on analyzing regulations and legal concepts related to Sharia stock benefit waqf in Indonesia and Malaysia. Legal sources include primary, secondary, and tertiary materials, with data collection techniques through literature study and data analysis using a comparative qualitative approach. The research results show that stock waqf has been implemented in Indonesia and Malaysia in accordance with applicable regulations, with differences in the institutional structure of its management. In Indonesia, stock waqf is regulated by the Ministry of Religion, the Indonesian Waqf Board, and the National Sharia Council, while in Malaysia it is managed by the State Islamic Religious Council in each state. Indonesia focuses on Sharia stock waqf or its profits, while Malaysia raises funds through share offerings to finance specific programs. Nevertheless, the potential for stock-based waqf in both countries has not been optimally maximized. Factors influencing development in Indonesia include stock waqf literacy, nazir capacity, and inefficient digitalization, while in Malaysia it is constrained by regulatory inconsistencies between states, lack of a transparent and accountable regulatory framework, and limited regulations on mechanisms for collecting and distributing cash waqf including shares.